Effect of Electric Field and Temperature on Average Structure and Domain Wall Motion in 0.93Bi0.5Na0.5TiO3-0.07BaTiO3 Ceramic - Jian Wang; Yun Liu; Andrew Studer; Lasse Norén; Ray Withers (Advances in Condensed Matter Physics)
In situ neutron powder diffraction patterns and dielectric spectra of 0.93Bi0.5Na0.5TiO3-0.07BaTiO3 ceramic were investigated under different electrical fields and temperatures. An electric-field-induced phase transition from metrically cubic to metrically tetragonal, associated with strong domain wall motion, occurs. Such induced phase and domain wall motion are unchanged until the high-temperature phase transition occurs from metrically tetragonal to metrically cubic. All these changes are irrelevant to the observed depolarization temperature (75°C). The depolarization behaviour is thus suggested to be associated with the local structure caused by the octahedral tilt twinning disorder.